2000
DOI: 10.1038/sj.onc.1203687
|View full text |Cite
|
Sign up to set email alerts
|

Growth Regulated Oncogene-α expression by murine squamous cell carcinoma promotes tumor growth, metastasis, leukocyte infiltration and angiogenesis by a host CXC Receptor-2 dependent mechanism

Abstract: Growth Regulated Oncogene-a (GRO-a) is an autocrine growth factor in melanoma and is a member of the C-X-C family of chemokines which promote chemotaxis of granulocytes and endothelia through binding to CXC Receptor 2. We found previously that variants of murine squamous cell carcinoma PAM 212 which grow and metastasize more rapidly in vivo constitutively express increased levels of murine GRO-a, designated mGRO-a, or KC. We have examined the possible role of mGRO-a expression in malignant progression of squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
135
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 15 publications
10
135
0
1
Order By: Relevance
“…Differential roles of CXCR1 and CXCR2 in endothelial cell migration have been reported previously (Li et al, 2002. It was shown that the migration of CXCR1-and CXCR2-expressing endothelial cells is predominantly mediated through CXCR2 (Addison et al, 2000;Loukinova et al, 2000; Heidemann et al, 2003). On the other hand, a recent report suggests that in melanoma cells, CXCL-8-mediated chemotaxis is mainly mediated through CXCR1 (Ramjeesingh et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Differential roles of CXCR1 and CXCR2 in endothelial cell migration have been reported previously (Li et al, 2002. It was shown that the migration of CXCR1-and CXCR2-expressing endothelial cells is predominantly mediated through CXCR2 (Addison et al, 2000;Loukinova et al, 2000; Heidemann et al, 2003). On the other hand, a recent report suggests that in melanoma cells, CXCL-8-mediated chemotaxis is mainly mediated through CXCR1 (Ramjeesingh et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…One consequence of this dysregulated NF-κB activity 23,55-58,61-68 is that there is constitutive transcription of the NF-κB-dependent chemokines CXCL1 and CXCL8 in human tumours [90][91][92][93][94][95][96] . Constitutive expression of these chemokines can transform immortalized melanocytes and is associated with increased metastasis in colon carcinoma, squamous-cell carcinoma and melanoma 19, 28,91,97 .…”
Section: Activation Of Nf-κb Enhances Chemokine Transcriptionmentioning
confidence: 99%
“…One of the most important functions of chemokine receptors is to mediate the chemotactic response of the chemokine receptor-expressing cells (Mehrad et al, 1999), which is essential for the recruitment of leukocytes to inflammatory site (Garcia-Ramallo et al, 2002;Mariani and Panina-Bordignon, 2003) and is likely important for the metastasis of cancer cells (Loukinova et al, 2000;Muller et al, 2001;Mashino et al, 2002). Vesicle recycling of chemokine receptors, including CXCR2, has been implicated in chemotaxis (Perez et al, 1986(Perez et al, , 1987(Perez et al, , 1989Zaslaver et al, 2001).…”
Section: Molecular Biology Of the Cell 2464mentioning
confidence: 99%
“…These results are consistent with the previous data showing the inhibition of the recycling of several other receptors, such as transferrin receptor and M4 muscarinic receptor, by the expression of myosin Vb tail or Rab11-FIP2 (129 -512) Hales et al, 2002;Volpicelli et al, 2002). The inhibition of the receptor recycling is likely due to the condensation of the recycling system induced by the expression of the mutant myosin Vb or Rab11-FIP2 secondary to the exit from the recycling system.One of the most important functions of chemokine receptors is to mediate the chemotactic response of the chemokine receptor-expressing cells (Mehrad et al, 1999), which is essential for the recruitment of leukocytes to inflammatory site (Garcia-Ramallo et al, 2002;Mariani and Panina-Bordignon, 2003) and is likely important for the metastasis of cancer cells (Loukinova et al, 2000;Muller et al, 2001;Mashino et al, 2002). Vesicle recycling of chemokine receptors, including CXCR2, has been implicated in chemotaxis (Perez et al, 1986(Perez et al, , 1987(Perez et al, , 1989Zaslaver et al, 2001).…”
mentioning
confidence: 99%